Phytochromes are key regulators of abiotic stress responses in tomato - Gavassi, Marina A. [UNESP]; Monteiro, Carolina C. [UNESP]; Campos, Marcelo Lattarulo; Melo, Hyrandir C.; Carvalho, Rogerio F. [UNESP] (Elsevier B.V., 2017)
Phytochromes are the best characterized and most frequently studied plant photoreceptors. A plethora of studies have revealed important roles for phytochromes in plant development, and more recently, evidence indicates that these photoreceptors also modulate responses to a multitude of abiotic and biotic stresses. Thus, the present work aimed to investigate whether tomato phytochromes phyA, phyB1 and phyB2 are involved with responses to low water potential (polyethylene glycol 6000 at Psi(W) of -0.3 MPa), high salinity (100 mM NaC1), cadmium contamination (65 mM CdCl2), high temperature (42 degrees C for six hours during three days) and ultraviolet B radiation (UV-B - 280-320 urn for eight hours during three days) stresses. For this purpose, seedlings of tomato mutants impacted by phytochrome A (fri), phytochrome B1 (tri) and phytochrome B2 (phyB2) were subjected to abiotic stresses and evaluated for their growth, pigment and osmoprotectant accumulation and lipid peroxidation. Under the conditions of this study, the results did not shown large variations of phyA mutant when compared to the wild genotype. However, the tomato phytochromes B1 and B2 mainly act as negative regulators of growth, pigment maintenance and osmoprotectant accumulation during responses to the different abiotic stresses.
Keywords: Abiotic stress; Mutants; Phytochromes; Photomorphogenesis; Tomato